2014
DOI: 10.1159/000368070
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Needle Aspiration Cytology of Mammary Analog Secretory Carcinoma Masquerading as Low-Grade Mucoepidermoid Carcinoma: Case Report with a Review of the Literature

Abstract: Background/Aim: The primary role of fine-needle aspiration cytology (FNAC) of salivary gland masses is to determine the underlying process and guide further management. The objective of our study is to provide a comprehensive review of cytologic features and ancillary studies of mammary analog secretory carcinoma (MASC), discuss differential diagnosis and review recent advances in the understanding of its biologic behavior. Case: A 23-year-old female underwent ultrasound-guided FNA of a slowly enlarging paroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Epidermoid cells and the immunophenotype (positive CK5/6 and p63 and triple‐negative) may also be confused with squamous metaplasia or a squamous metaplastic carcinoma. Lastly, low‐grade MEC could be mistaken for secretory carcinoma, another rare salivary gland‐type carcinoma . Both tumours can have a prominent cystic component, abundant PAS‐D‐positive secretory material and cytologically bland cells which may have eosinophilic, clear or vacuolated cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidermoid cells and the immunophenotype (positive CK5/6 and p63 and triple‐negative) may also be confused with squamous metaplasia or a squamous metaplastic carcinoma. Lastly, low‐grade MEC could be mistaken for secretory carcinoma, another rare salivary gland‐type carcinoma . Both tumours can have a prominent cystic component, abundant PAS‐D‐positive secretory material and cytologically bland cells which may have eosinophilic, clear or vacuolated cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, low-grade MEC could be mistaken for secretory carcinoma, another rare salivary gland-type carcinoma. 41 Both tumours can have a prominent cystic component, abundant PAS-D-positive secretory material and cytologically bland cells which may have eosinophilic, clear or vacuolated cytoplasm. In addition, both are immunohistochemically positive for mammaglobin, MUC4 and CK5/6 and negative for ER, PR and HER2.…”
Section: Discussionmentioning
confidence: 99%
“…From then on, revisiting the medical literature, retrospective studies, and case reports were integrated to scout the incidence of MASC SG . This systematic review surveys almost all the reported cases, after omitting the repeated cases, in order to define our nosology about MASC SG . In 2013, Sethi et al concluded that MASC SG was claimed to be encountered in men more than in women.…”
Section: Introductionmentioning
confidence: 99%
“…Papillary architecture with transgressing vessels, microcystic pattern along with bubbly cytoplasm, lack of intermediate and squamous cells facilitate the distinction from MEC [14][15][16][17][18][19][20] (Table III) Table IV. IHC and molecular studies are useful in differentiating MASC from its mimics and confirming the diagnosis. However, predominant microcystic pattern with eosinophilic secretions, abundant bubbly cytoplasm, cells with single intra-cytoplasmic mucin vacuole and cellular hob nailing facilitate distinction form acinic AcCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, predominant microcystic pattern with eosinophilic secretions, abundant bubbly cytoplasm, cells with single intra-cytoplasmic mucin vacuole and cellular hob nailing facilitate distinction form acinic AcCC. Papillary architecture with transgressing vessels, microcystic pattern along with bubbly cytoplasm, lack of intermediate and squamous cells facilitate the distinction from MEC [14][15][16][17][18][19][20] (Table III). Thus, one can suspect the possibility of MASC based on these cytomorphological features on FNAC.…”
Section: Discussionmentioning
confidence: 99%